Model Pemberdayaan Ekonomi Berbasis Pesantren: Studi Kasus Unit-Unit Kewirausahaan di Pondok Pesantren Bahrul Maghfiroh Kota Malang - Reza Ahmad Aulia; Dwi Wulandari (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Pesantren as the oldest Islamic educational institution in Indonesia certainly has an important role in society. Today pesantren are required to be able to develop more without having to eliminate the characteristics of pesantren. One of them is by holding empowerment for pesantren independence and a place to practice entrepreneurship for students. This study aims to determine the model of pesantren-based economic empowerment at the Bahrul Maghfiroh Islamic Boarding School in Malang City with the existence of business units in the fields of agriculture, fisheries and services. This research uses a case study method with a qualitative approach. Techniques Data collection is done by means of interviews, observation and documentation. The results of the study show that all business units here are managed by students and accompanied by a team of experts in each business field. First, the preparation stage. Preparation for the formation of business units is carried out by analyzing the strength of PPBM and market competition. Second, the implementation phase of the business unit begins with recruiting members and providing education and marketing methods. Third, evaluation and monitoring. As an evaluation material, supervision is carried out by the Islamic boarding school. With the existence of this business unit, it is in order to equip students when they are in the community and later they can practice what they have got. Some of the obstacles faced were related to human resources, facilities and infrastructure as well as the increase in the price of production goods. The solution is to increase education to college level and increase sales prices.